The zymogen-enteropeptidase system: A practical approach to study the regulation of enzyme activity by proteolytic cleavage - Pizauro, J. M.; Ferro, J. A.; de Lima, ACF; Routman, K. S.; Portella, M. C. (Amer Soc Biochemistry Molecular Biology Inc, 2004)
The present research describes an efficient procedure to obtain high levels of trypsinogen and chymotrypsinogen by using a simple, rapid, and easily reproducible method. The extraction process and the time-course of activation of zymogens can be carried out in a single laboratory period, without sophisticated equipment. The main objective was to prepare a laboratory class that would stimulate student interest in enzyme regulation, exploring the fact that the catalytic activity of some enzymes is regulated by different mechanisms. The regulation of proteolytic enzymes requires the synthesis of an inactive zymogen and its being irreversibly switched on by specific proteolytic cleavage.
Keywords: zymogen; trypsin; chymotrypsin; enteropeptidase; enzyme regulation; proteolytic cleavage